Nutritional Status of Dengue Haemorrhagic Fever in Children - Sugiyanto Sugiyanto; Teluk Sebodo; Sutaryo Sutaryo; Sumanto Sumanto; Ismangoen Ismangoen (Indonesian Pediatric Society, 1983)
Shock in Dengue infection is especially caused by an immunologic process (secondary reaction). This process may occur when the activity of Lymphocytes (C.M.l.), complement system and macrophages is good. This activity, however is disturbed in undernutrition. In this study on 126 DHF/DSS patients, fulfilling the WHO criteria (1975), the cases of shock were mostly found in patients with a body weight of more than 80% Harvard standard. There was no case of shock, in patients with a nutritional status under 60% of the Harvard standard.